Anti Black Market cartoon, 1942 (1942)
1942 1939-1945 "Anti Black Market cartoon, 1942" [HFR0080], 1942 Cartoon by Batt showing a Black Market octopus strangling the war effort through thefts from docks and railway yards. This cartoon appeared in the National Union of Railwaymen Railway Review, 13 March, 1942.